Implementation of On-Page and Off Page SEO to Improve Tourism Promotion Websites - Akbar, Ahmad; Sulistianingsih, Indri; Syam, Fariz Harindra; Kurniawan, Bagus (International Conference on Sciences Development and Technology, 2022)
Promotion for Kota Pari Village. Effective search engine optimization (SEO) is crucial for increasing online visibility and attracting potential tourists in an increasingly digital world. The research examines the strategic implementation of on-page SEO, with a focus on keyword research, content quality, page optimization, mobile-friendliness, and internal linking. In addition, this paper examines off-page SEO techniques, such as link building, local citations, social media marketing, online reviews, guest blogging, and local collaborations. By employing a combination of these techniques, tourism stakeholders in Kota Pari Village can effectively market their attractions, events, and experiences, ultimately driving organic traffic and fostering the tourism industry's sustainable growth